Occupational Therapy Services in School-Based Practice: A Pediatric Occupational Therapy Perspective from Ireland - Carol O'Donoghue; Jennifer O'Leary; Helen Lynch (Hindawi-Wiley, 2021)
Purpose. School is a primary setting for pediatric occupational therapy practice, yet little is known about the provision of school-based occupational therapy in many countries internationally. The purpose of this study was to explore current school-based occupational therapy practice for the first time in Ireland to gain insight into current and potential service provision and to identify new directions and potential pathways for development. Methods. This descriptive quantitative study utilized a cross-sectional online survey to gain the perspectives of the population of pediatric occupational therapists working regularly in schools across Ireland. Respondents were recruited through convenience and snowball sampling. Data were analysed through qualitative content analysis and descriptive statistics. Results. The survey elicited 35 responses, yielding a 21.2% estimated response rate. Findings demonstrated that respondents provided therapy services in schools most commonly on a weekly (28.6%) or monthly (34.3%) basis, with only 5.0% working in the same school on a weekly or fortnightly basis. The majority of respondents (54.3%) used a direct therapy approach with a child, rather than coaching or modelling, to primarily address sensory, hand function, or daily living needs. None used a whole class or whole school (universal or tiered) approach. While respondents (54.3%) generally viewed collaborative practice as a strength of school-based practice, they also identified barriers to collaboration in schools. A core barrier is related to how services are constructed across health and education, with differing philosophies of service provision. The majority of respondents (75.0%) reported that they had not received any training to deliver evidence-based practice in therapy provision specific to school-based practice. Implications for Practice. This study indicates that therapists require continual education on evidence-based school practice as it applies in an Irish context. Furthermore, clarification of school therapy roles and service delivery models are required in order to determine how they contrast with traditional clinic roles. This will enable therapists to strengthen the coordination of service delivery between health and educational services to maximize the outcomes of school-based practice.